Pengaruh Kualitas Layanan, Kualitas Produk dan Harga Melalui Brand Image Terhadap Keputusan Pembelian di Outlet Coffee Shop Pada Generasi Z - Ragilia Asri Putri; Primasatria Edastama (International Forum of Researchers and Lecturers, 2023)
The purpose of this research is to find out and understand the things that can encourage purchasing decisions for a product in a coffee shop, namely service quality, product quality, and price accompanied by a brand image. The population and sample in this study were 125 respondents who made purchases at coffee shop outlets at least twice in the last 1 month, aged 18-25 years, and domiciled in DKI Jakarta. The analytical method used is the Structural Equation Model (SEM). In this study it was found that service quality, product quality, price and brand image influence purchasing decisions. And for service quality, product quality and price affect brand image. Based on the results of this study, the coffee shop must maintain and improve the quality of service which is considered good in providing satisfaction for its customers. After that, the product strategy implemented by the coffee shop is to prioritize the quality of taste and characteristics that are not found in other products so that consumers are attracted. Then, in terms of price, it is expected that the coffee shop will set a more affordable price, compared to the prices of other products.